Behavioral influences on driver crash risks in Ghana: A qualitative study of commercial passenger drivers. (17th February 2019) - Dotse, John; Nicolson, Rod; Rowe, Richard
Abstract: Objectives: Though there is a growing body of literature on crash risks in the developed world, little is known about how well these models apply to motoring in developing countries, the context in which the majority of road traffic fatalities occur. This qualitative study explores factors perceived to influence crash risks for commercial drivers in Ghana. Method: Twenty commercial drivers of varied ages and experience were sampled from 7 major lorry terminals in 3 regions (Greater Accra, Ashanti, and Volta) of Ghana. Data were collected through semistructured interviews. Results: The participants identified some issues that are shared with drivers in the developed world, though moderated by the Ghanaian context. These included work pressures (e.g., fatigued driving), speeding, distracted driving, and inadequate vehicle maintenance. Other factors identified by participants are less frequently considered in research addressing driving behavior in developed countries. These included aggressive competition over passengers and corruption (e.g., improper licensing practices), among others. Conclusion: The findings have implications for building a research base to support the development of road safety policy and interventions in developing countries.